The Handbook of Communication and Security - Taylor, Bryan C; Bean, Hamilton (ICA Handbook Series, 2019)
The Handbook of Communication and Security provides a comprehensive collection and synthesis of communication scholarship that engages security at multiple levels, including theoretical vs. practical, international vs. domestic, and public vs. private. The handbook includes chapters that leverage communication-based concepts and theories to illuminate and influence contemporary security conditions. Collectively, these chapters foreground and analyze the role of communication in shaping the economic, technological, and cultural contexts of security in the 21st century. This book is ideal for advanced undergraduate and postgraduate students and scholars in the numerous subfields of communication and security studies.